Pittsburgh as a High Risk Population: The Potential Savings of a Personalized Dental Care Plan - Andrew J. Ng; Alexandre R. Vieira (Hindawi Limited, 2016)
Objectives. Little evidence exists for the current standard of two annual preventative care visits. The purpose of this study was investigate this claim by modeling the potential savings of implementing a personalized care plan for high risk individuals in the Pittsburgh region. Methods. Using radiographs from 39 patients in the University of Pittsburgh Dental Registry and DNA Repository database, two models were created to analyse the direct savings of implementing a more aggressive preventative treatment plan and to view the longitudinal cost of increased annual yearly visits. Results. There is a significant decrease (p<0.001) between original and modeled treatment cost when treatment severity is reduced. In addition, there is a significant decrease in adult lifetime treatment cost (p<0.001) for up to four annual visits. Conclusions. Patients in high risk populations may see significant cost benefits in treatment cost when a personalized care plan, or higher annual preventative care visits, is implemented.